Reconstrucción fonológica del pidgin afroportugués americano: La s consonantes. - Portilla Chaves, Mario (2012)
This article provides the proto-conosonant reconstruction of an Afro-Portuguese pidgin spoken in the Americas in the XVII Century according to the principles of the Historical Comparative Method.